Drawing On The Postcolonial reading Of Europe’s Quandary On The Muslim(s) at Home - June Cahyaningtyas (Jurnal Paradigma, 2016)
For the past thirty years Europe faces tumultuous counter action that appears to threaten the normative ideal of European institution. Driven by the call of recognition and acknowledgement, post-colonial migrants have posed a question on the basic presumption that bound European societies for long. Approach to assimilation, integration and multicultural society, appears to be inadequate to appeal migrants submit in the mainstream value. Demographically, ideologically and mythically threatening, Muslims are at the most part stand affront the greater challenge for European culture. The paper tries to bring to light the discourse that set this threat appearance come into being in European public sphere. Taking post-colonial on loan of description, the paper claim to overview the need to re-course the relations between Muslims and Europe, and the way discourse on Islam can be practiced in between.